Plural strategies and devices in Igbo (2016)
This study examines strategies and devices adopted in Igbo to mark plurality on lexical items at both word and phrasal levels. The study provides additional evidence, adequate description, and explanation, as well as a theoretical background to the phenomenon which hitherto was not provided by earlier studies. Data were collected through observation, oral interview, and from existing literature. Data were analysed based on the principles and operations of the Minimalist Program. The study finds that five basic strategies could be employed to mark plurality in Igbo. These include merging of singular nouns with plural words or morphemes, via reduplication, use of conjunctions, use plural sensitive verbs, and context of speech. Plural devices include nouns with an inherent PL feature such as ndi ‘persons’ and umu ‘offspring’; the third person plural pronoun, ha; quantifiers such as niile/dum ‘all’; numerals abuo ‘two’ and above; mass nouns, igwe/igwurube ‘group’; clitics ga and nu ; reduplicated nouns; conjunctions na ‘and’; and plural-sensitive verbs such as chita ‘bring’, and ju, ‘be’. The study concludes that Igbo belongs to the set of languages that syntactically mark plural by using independent morphemes/words; i.e. plural words.